Toward a Digital Health Intervention for Vestibular Rehabilitation: Usability and Subjective Outcomes of a Novel Platform - Meldrum, Dara; Murray, Deirdre; Vance, Roisin; Coleman, Sarah; McConnell, Sonya; Hardiman, Orla; McConn Walsh, Rory (Frontiers in Neurology, 2022)
Digital technologies are increasingly available and are reducing in cost. There is an opportunity to move to a digital health approach in vestibular rehabilitation but there is paucity of suitable systems available and consequent lack of evidence to support their use. This study aimed to investigate a novel digital platform developed specifically for vestibular rehabilitation (comprising clinician software, a wearable sensor, and a patient facing app). Participants (n=14 9F:5M mean age 59) with a confirmed unilateral peripheral vestibular dysfunction and imbalancehypofunction used the app for treatment and therapists (n=4) used the platform to deliver vestibular rehabilitation in the form of individualised exercise programs over a mean of 17.4±8.8 weeks. Outcomes included the System Usability Scale (SUS), the Patient Enablement Instrument (PEI), change in subjective symptoms (numerical rating scales), percentage adherence to prescribed exercise and a semi structured interview on utility. A significant reduction was found in symptoms of vertigo/dizziness (p<0.004), imbalance (p<.002), oscillopsia (p<0.04), and anxiety (p<0.02) after use. System Usability Scores were high for both clinicians (mean 85/100) and participants (mean 82.7/100) and high enablement was reported (mean PEI 6.5/12). Overall percentage adherence to the exercise prescription when measured digitally was highly variable and ranged from (4%-77%). At semi structured interviews participants reported a high level of acceptance and satisfaction with digital delivery and no adverse events were recorded. When COVID-19 restrictions eased, 2 participants trialled the head sensor and found it highly usable. Further work research is required to investigate efficacy and how the sensor impacts care.